2024
DOI: 10.1117/1.apn.3.1.016011
|View full text |Cite
|
Sign up to set email alerts
|

Dual-channel quantum meta-hologram for display

Yubin Fan,
Hong Liang,
Yuhan Wang
et al.

Abstract: .Quantum technologies rely on creating and manipulating entangled sources, which are essential for quantum information, communication, and imaging. By integrating quantum technologies and all-dielectric metasurfaces, the performance of miniature display devices can be enhanced to a higher level. Miniature display technology, such as virtual reality display, has achieved original commercial success, and was initially applied to immersive games and interactive scenes. While the consumer market has quickly adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recently, studies in metasurfaces have shown that integrated-resonant units (IRUs) present a promising solution to overcome the existing bottleneck in field enhancement. By integrating various resonance modes within one supercell, the IRU not only leverages the intrinsic modes for field enhancement but also promotes interactions among these modes, significantly amplifying the electric field. Furthermore, IRU is capable of engaging nonlocal resonance modes characterized by a collective response from multiple adjacent units .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies in metasurfaces have shown that integrated-resonant units (IRUs) present a promising solution to overcome the existing bottleneck in field enhancement. By integrating various resonance modes within one supercell, the IRU not only leverages the intrinsic modes for field enhancement but also promotes interactions among these modes, significantly amplifying the electric field. Furthermore, IRU is capable of engaging nonlocal resonance modes characterized by a collective response from multiple adjacent units .…”
Section: Introductionmentioning
confidence: 99%